New insights into telomeric DNA sequence (TTAGGG)n location in bat chromosomes - Faria, K. C.; Marchesin, S. R C [UNESP]; Moreira, P. R L [UNESP]; Beguelini, M. R. [UNESP]; Morielle-Versute, E. [UNESP] (Genetics and Molecular Research, 2009)
Molossidae species, Cynomops abrasus (2n = 34, fundamental number, FN = 64), Eumops auripendulus (2n = 42, FN = 62), Molossus rufus (2n = 48, FN = 64), Molossops temminckii (2n = 48, FN = 64), and Nyctinomops laticaudatus (2n = 48, FN = 64), and Phyllostomidae species, Phyllostomus discolor (2n = 32, FN = 60), have karyotypes with different chromosome and fundamental numbers, different localization of constitutive heterochromatin, and different numbers and location of nucleolar organizer regions (NORs). Fluorescence in situ hybridization with a human probe of the telomeric sequence (TTAGGG)n produced fluorescent signals in telomeric regions of the six bat species' chromosomes; in E. auripendulus, pericentromeric signals were also observed in the acrocentric and subtelocentric chromosomes. A relationship between telomeric sequences and NORs, and between telomeric sequences and constitutive heterochromatin was detected in chromosomes bearing NORs in C. abrasus, M. temminckii, N. laticaudatus, and P. discolor. No interstitial signal was observed in the meta- or submetacentric chromosomes of these species. ©FUNPEC-RP.
Keywords: Chiroptera; Fluorescence in situ hybridization; Molossid; Phyllostomid; Telomeric sequence; acrocentric chromosome; animal cell; bat; chromosome analysis; chromosome NOR; DNA sequence; fluorescence; fluorescence in situ hybridization; gene location; heterochromatin; karyotype; molecular probe; nonhuman; sequence analysis; signal transduction; species composition; species difference; telomere; Animals; Base Sequence; Chromosome Banding; Chromosomes, Mammalian; Molecular Sequence Data; Nucleolus Organizer Region; Telomere; Cynomops; Eumops auripendulus; Molossidae; Molossops temminckii; Molossus rufus; Nyctinomops laticaudatus; Phyllostomidae; Phyllostomus discolor